DISKRIMINASI HARGA BERDASARKAN GENDER : PRODUK DI INDONESIA - Aida Rakhmawati; Sasiska Rani (Jurnal RATRI (Riset Akuntansi Tridinanti), 2022)
The phenomenon that arises today is the existence of product innovations that are specifically intended for certain genders (pink products) and (blue products) which are subject to higher prices than unisex products. Especially for products that are packaged for the feminine consumer market or pink products. This phenomenon became known as the Pink Tax where products marketed for the feminine or female gender tend to be twice as expensive as men's products. Scientific writing is carried out using a descriptive method using a qualitative approach which aims to explain the meaning behind the social reality that occurs. The gender perspective is then used to see the problems that arise in the form of price gaps based on gender-labeled products. The results of this study conclude that gender labeling on the product itself is a method used by industry and sellers to classify or segment their consumers. The phenomenon of pink tax itself for industry owners and sellers is a gap to get more profits.Keywords: Price discrimination; Gender; Pink Tax.